Increased Expression of Angiotensin II Type 2 Receptors in the Solitary-Vagal Complex Blunts Renovascular Hypertension - Blanch, Graziela Torres [UNESP]; Freiria-Oliveira, Andre Henrique [UNESP]; Fina Speretta, Guilherme Fleury [UNESP]; Carrera, Eduardo J.; Li, Hongwei; Speth, Robert C.; Colombari, Eduardo [UNESP]; Sumners, Colin; Colombari, Debora S. A. [UNESP] (Lippincott Williams & Wilkins, 2014)
Angiotensin II increases and decreases arterial pressure by acting at angiotensin type 1 and type 2 receptors, respectively. Renovascular hypertensive rats exhibit a high level of activity of the peripheral and central renin-angiotensin system. Therefore, in the present study, we evaluated the effect of increasing the expression of angiotensin type 2 receptors in the solitary-vagal complex (nucleus of the solitary tract/dorsal motor nucleus of the vagus), a key brain stem region for cardiovascular regulation, on the development of renovascular hypertension. Holtzman normotensive rats were implanted with a silver clip around the left renal artery to induce 2-kidney 1-clip renovascular hypertension. Three weeks later, rats were microinjected in the solitary-vagal complex with either an adenoassociated virus to increase the expression of angiotensin type 2 receptors or with a control vector. We observed that increasing angiotensin type 2 receptor expression in the solitary-vagal complex attenuated the development of renovascular hypertension and also reversed the impairment of the baroreflex and the increase in the low-frequency component of systolic blood pressure observed in renovascular hypertensive rats. Furthermore, an observed decrease in mRNA levels of angiotensin-converting enzyme 2 in the solitary-vagal complex of renovascular hypertensive rats was restored to control levels after viral-mediated increases in angiotensin type 2 receptors at this site. Collectively, these data demonstrate specific and beneficial effects of angiotensin type 2 receptors via the brain of hypertensive rats and suggest that central angiotensin type 2 receptors may be a potential target for therapeutics in renovascular hypertension.
Keywords: angiotensin II; angiotensin-converting enzyme 2; angiotensin receptor blockers; baroreflex